Implementasi Perbaikan Proses Spot Welding melalui Integrasi Teknologi Industri 4.0 dan Pokayoke untuk Meningkatkan Kualitas dan Stabilitas Produksi - Pratama, Adidya Rangga; Prabawani, Bulan (UII, 2026)
PT X faced quality challenges in its spot-welding process, resulting in a high product defect rate and reduced competitiveness. Reliance on manual processes led to inconsistencies, which impacted customer satisfaction and the company's reputation. To address this issue, researchers initiated an Industry 4.0 based transformation with a Six Sigma approach. Improvements were made by implementing servo robots to automate the spot-welding process. This step was accompanied by modifications to the jig, the use of Jundate pallets, and the adoption of Zirconium cup tips to overcome downtime due to sticking. As a result, the company succeeded in significantly reducing the DPMO from 255 to 12, increasing productivity by 16%, and generating significant annual cost savings. In addition to tangible benefits, these improvements also resulted in increased customer trust, the acquisition of new projects, and an improved corporate image.